2017
DOI: 10.1038/nrneurol.2017.122
|View full text |Cite
|
Sign up to set email alerts
|

Brain imaging tests for chronic pain: medical, legal and ethical issues and recommendations

Abstract: 624 | OCTOBER 2017 | VOLUME 13 www.nature.com/nrneurol CONSENSUS STATEMENT © 2 0 1 7 M a c m i l l a n P u b l i s h e r s L i m i t e d , p a r t o f S p r i n g e r N a t u r e . A l l r i g h t s r e s e r v e d . NeuroethicsA field that studies the implications of neuroscience for human self-understanding, ethics, and policy. Arterial spin labellingAn MRI-based brain imaging technique that detects cerebral blood flow based on magnetic tagging of blood.Nevertheless, diverse groups -including patients, resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
195
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 251 publications
(203 citation statements)
references
References 116 publications
(158 reference statements)
4
195
0
4
Order By: Relevance
“…Future studies need to take potential muscle confounds into account, but might investigate the potential of prefrontal gamma activity as a marker of ongoing pain for the diagnosis and treatment of chronic pain (Davis et al, 2017), especially in the context of neurofeedback and neurostimulation treatment approaches (Jensen et al, 2014;Sitaram et al, 2017;Thut et al, 2017). Thus, they reveal a potential neurophysiological marker of ongoing pain, which could be measured relatively easily using EEG as a noninvasive and broadly available clinical tool.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future studies need to take potential muscle confounds into account, but might investigate the potential of prefrontal gamma activity as a marker of ongoing pain for the diagnosis and treatment of chronic pain (Davis et al, 2017), especially in the context of neurofeedback and neurostimulation treatment approaches (Jensen et al, 2014;Sitaram et al, 2017;Thut et al, 2017). Thus, they reveal a potential neurophysiological marker of ongoing pain, which could be measured relatively easily using EEG as a noninvasive and broadly available clinical tool.…”
Section: Discussionmentioning
confidence: 99%
“…They are furthermore in line with a role of emotional-evaluative circuits rather than sensory circuits in ongoing pain, emphasizing the emotional aspects of the chronic pain experience. Future studies need to take potential muscle confounds into account, but might investigate the potential of prefrontal gamma activity as a marker of ongoing pain for the diagnosis and treatment of chronic pain (Davis et al, 2017), especially in the context of neurofeedback and neurostimulation treatment approaches (Jensen et al, 2014;Sitaram et al, 2017;Thut et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have shown that neuroimaging can further our understanding of chronic pain and can help us to define new therapeutic options/targets (for a consensus paper, see ref. ). Insights from neuroimaging studies could also open the field of neuromodulation for other pain disorders, for example diabetic neuropathic pain.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, a potential lack of specificity does not necessarily limit the clinical usefulness and validity of a brain-based marker of chronic pain (see [18] for an in-depth discussion of criteria for brain-based markers of chronic pain). In fact, many well-established laboratory, electrophysiological and imaging tests yield results which are neither disease-specific nor symptom-specific, but are clinically highly useful.…”
Section: Discussionmentioning
confidence: 99%